Effect of Baffle on Heat Transfer Performance of Turbine Blade Composite Cooling Channel Based on Latticework - Minlong Li; Ke Yang; Huishe Wang; Rongguo Yu; Jingze Tong (Machines)
Using the numerical simulation of the Reynolds-averaged Navier–Stokes method, the effects of two new baffle structures on the heat transfer performance of a composite cooling structure based on latticework in the leading-edge region and the mid-chord region of the turbine blade were studied. Further, the heat transfer performance of the composite cooling structure caused by the difference between the rectangular channel and the wedge channel is compared. The application potential of the new baffle is comprehensively evaluated, which provides design experience for the application of the baffle in the composite cooling structure of the leading-edge region and the mid-chord region of the turbine blade. It is found that the baffle significantly improves the comprehensive heat transfer capacity and flow rate in the leading-edge channel region and the mid-chord channel non-transition region. The baffle increases the comprehensive heat transfer coefficient of the leading-edge channel by 26.5% and the flow rate by 14.5%. The baffle leads to an increase in the comprehensive heat transfer coefficient and flow rate in the mid-chord channel non-transition region by 39.5% and 6.5%, respectively. However, the baffle significantly restrains the heat transfer in the mid-chord channel transition region, resulting in an average decrease of 16.5% in the flow rate in this region. The comprehensive heat transfer performance of the continuous baffle is 4.7% higher than that of the discontinuous baffle, and the heat transfer uniformity of the composite channel based on the continuous baffle is better. Compared with the rectangular channel, the baffle increases the difference in flow distribution in each region of the wedge channel, but the effect of the baffle on the heat transfer performance parameters of the wedge channel is weakened, and the heat transfer distribution is more uniform.